Factor Replacement Treatment for Hemophilia A: Achievements and Perspectives - Mancuso, Maria Elisa (Seminars in Thrombosis and Hemostasis, 2024)
The mainstay of treatment for persons with hemophilia A (PwHA) with severe bleeding phenotype is prophylaxis. The pharmacokinetic (PK) profile of native factor VIII (FVIII) imposes the need for rather frequent intravenous injections to ensure effective prophylaxis, but this represents a relevant treatment burden and is associated with suboptimal adherence to treatment. In this light, the advent of extended half-life (EHL) FVIII molecules has improved prophylaxis feasibility and outcomes by favoring treatment individualization and tailoring protection according to specific clinical and nonclinical needs. Different technologies have been used to enhance FVIII PK properties including Fc-fusion and conjugation with polyethylene glycol. Data from clinical development programs for such molecules, together with growing real-world experience, have shown numerous benefits related to the use of EHL FVIII in PwHA. Recently a new class of ultra-long-acting EHL FVIII has been developed to further improve protection against bleeding episodes and achieve the ambitious goal of providing PwHA with hemostatic protection in the nonhemophilia range over longer time periods, hence ensuring very low bleeding rates and improving joint health and quality of life. In this review, the achievements and perspectives of replacement therapies for PwHA are summarized and discussed.
Keywords: hemophilia A; factor VIII; EHL-FVIII; efanesoctocog alfa; prophylaxis